Correct feeding organization is an important reserve for increasing meat production - Durdona Abduzoirova (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The article discusses the hanging technology of the mutton production in the foothill breeding sheep zone of different genotypes